IBSEN’S LITTLE EYOLF: THE GREAT EFFORTS OF A HANDICAP CHILD IN ACHIEVING HIS SELF – ACTUALIZATION NEEDS - Imam Basuki; Fafan S. (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
This article discusses about Little Eyolf , a drama written by Henrik Ibsen , telling about a handicapped child, named Eyolf, who is hard enough to find his self-actualization because his parents and neighborhoods give him poor affection. To study this phenomenon, the inductive method is applied to analyze the self-actualization. The study focuses on Eyolf’s self actualization and aims to fid out how Eyolf gets his self actualization in his life. By the unsupportive environment, Eyolf escapes from reality and lives in his world of fantasy to fulfill his own need. The spirit of Eyolf to find his own redemption is closely related to the Maslow’s hierarchy of needs. Therefore, in this study is applied qualitative research. Eyolf’s dying spirit of self-actualization ends with tragedy. However, in this final scene, his parents regrets not giving Eyolf the needs for physiological, safety, self esteem, belongingness and love during his childhood. The result of the research proves that to achieve his self-actualization or the basic need of his life, Eyolf needs very much his parents’s care and affection but it is never happened during his childhood time.